"Carbolong" polymers with near infrared triggered, spatially resolved and rapid self-healing properties. Issue 3 (13th December 2018) - Zhang, Huan; Zhao, Haibo; Zhuo, Kaiyue; Hua, Yuhui; Chen, Jiangxi; He, Xumin; Weng, Wengui; Xia, Haiping
Abstract : Conjugated Möbius metalla-aromatic "carbolong" is incorporated into polymers to achieve spatially resolved, repeated and fast healing through a photothermal effect. Abstract : Metallopolymers combine the functionality of metal centres with the processabilities of polymers, leading to rapidly expanding interest in the design and development of novel functional materials and devices. Carbolong complexes are a brand-new family of Möbius metalla-aromatics among which specific structures exhibit excellent photothermal properties under near infrared (NIR) light. Here, NIR photothermally healable carbolong polyurethanes (CLPUs) carrying covalently embedded 12C-carbolong motifs in the backbone are reported for the first time. CLPUs with a very low content of 12C-carbolong (down to 0.10 wt%) exhibit fast (<1 min), spatially resolved, and repeatable (>5 cycles) healing whose efficiency can be tuned by the content of the carbolong complex and NIR power. The healing mechanism is ascribed to the accelerated dissociation of physical interactions, melting of polymer crystallites and chain diffusion induced by the NIR photothermal effect of carbolong embedded in the CLPUs. The fruitful chemistry and the unique photothermal properties of carbolong complexes make them versatile for the design of light-controlled and light-powered self-healing materials.